ANALISIS STRATEGI PENGEMBANGAN USAHA MENGGUNAKAN BUSINESS MODEL CANVAS (STUDI KASUS DI KOLAM BENIH DAN KONSUMSI PEMUDA PEMBUDIDAYA IKAN LELE CILEUNYI KABUPATEN BANDUNG) - Nababan, Leri; Nurhayati, Atikah; Rochima, Emma; Maulina, Ine (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
The purpose of this research is to analyze the business model of the Cileunyi Catfish Cultivation Youth Seed and Consumption Pool using the Business Model Canvas, and analyze the development strategy of the catfish farming business at the Cileunyi Catfish Cultivation Youth Seed and Consumption Pool. This research was conducted at the Catfish Cultivation Youth Seed and Consumption Pool, on Jalan Cibiru Beet Ds. Cileunyi Wetan Kec. Cileunyi Kab. Bandung, West Java. The research method used is a case study with a quantitative and qualitative approach. Data collection was carried out by observation, questionnaires, interviews, and literature studies. Respondents were taken by purposive sampling method with a total of 31 respondents. The analysis used is business model canvas analysis, and SWOT analysis. The results of the Business Model Canvas analysis, the authors identified key elements utilizing 9 variables, namely customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities and cost structures that contribute to the success of the catfish farming business. The results of the SWOT analysis obtained the position of the X axis (0.17) and the Y axis (0.38) are in quadrant I, which means that the strategy applied is an aggressive strategy (S-O), namely utilizing existing strengths to seize the maximum opportunity.